Performance of direct seeded rice (DSR) in relation to planting patterns and weed control methods on weed dynamics and productivity - Burra, Shyamsunder; Thulisekari, Prasanna; Ujagar, Singh Walia; Guntimadugu, Santhosh Kumar Raju (Plant Science Today, 2026)
Rice (Oryza sativa L.) is the major significant staple food of Indian population. Compared to puddled transplanting, direct seeded rice (DSR) is environmentally friendly but faces severe weed infestation and iron deficiency, resulting in low yields and poor farmer adoption. To examine these problems, a field study was conducted using a Split-Plot Design at Lovely Professional University, Punjab, India during 2022 and 2023. Different planting patterns were kept in main plots were flat sowing, two rows per bed, three rows per bed and two rows per bed and one in furrow and sub plots treatments were “pendimethalin fb. bispyribac, pendimethalin fb. metsulfuron, weed free up to harvest and unweeded (control)”. Among the planting patterns, three rows per bed produced significantly higher paddy yield than flat sowing. This treatment was followed by two rows on bed and one in furrow. Also weed density was lower in all bed planting treatments as compared to flat sowing technique due to deep burial of weed seeds. Among weed control treatments, unweeded (control) resulted in more than 95 % yield loss compared with herbicidal treated plots. Pre-emergence application of pendimethalin fb. post-emergence application of bispyribac showed better performance on typical non-paddy and paddy weeds i.e., grasses, sedges and broad leafed weeds in DSR and resulted in higher yields over other weed control treatments but weed free upto harvest treatment was found at par to this treatment during both years.